The Politics of Education in Developing Countries: From Schooling to Learning - PAJĄK-WAŻNA, EWA (Przegląd Krytyczny, 2020)
The issue of quality in education is still one of the key current debates within international education policy. There are comments that development education has a significant contribution to make to these debates. Skinner, Blum and Bourn (2013) suggested that greater collaboration between the field of development education and international education policy could facilitate the creation of an agenda that focuses on education quality and learning processes, as opposed to the current preoccupation with education access and outcomes.